2008
DOI: 10.1002/dmrr.797
|View full text |Cite
|
Sign up to set email alerts
|

SUMO4 and its role in type 1 diabetes pathogenesis

Abstract: Susceptibility to type 1 diabetes (T1D) is determined by interactions of multiple genes with unknown environmental factors. Despite the characterization of over 20 susceptibility regions for T1D, identification of specific genes in these regions is still a formidable challenge. In 2004, we first reported the cloning of a novel, small ubiquitin-like modifier (SUMO) gene, SUMO4, in the IDDM5 interval on chromosome 6q25, and presented strong genetic and functional evidence suggesting that SUMO4 is a T1D susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 107 publications
1
46
0
1
Order By: Relevance
“…The SUMO2/3 proteins are often conjugated to proteins in response to a signaling or stress stimulus (17,43). SUMO4 was recently identified, and polymorphisms of this isoform have been linked to several disease states (44,45); however, it remains ambiguous whether SUMO4 is a direct protein modifier or a pseudogene (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…The SUMO2/3 proteins are often conjugated to proteins in response to a signaling or stress stimulus (17,43). SUMO4 was recently identified, and polymorphisms of this isoform have been linked to several disease states (44,45); however, it remains ambiguous whether SUMO4 is a direct protein modifier or a pseudogene (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…The differences of diabetes incidence between groups were determined using the log-rank (Mantel-Cox) test. 2 test was used to determine the difference for insulitis severity at each time point. Comparisons between groups for flow cytometry, cytokine production, and intracellular cytokine expression were accomplished by one-way ANOVA using SPS 11.5 for Windows.…”
Section: Conclusion-extracellularmentioning
confidence: 99%
“…Interestingly, the number of CD8 ϩ interferon-␥ ϩ (Tc1) T-cells was increased in the PLNs and spleen after blockade of HMGB1, which could be associated with retarded migration of activated autoreactive T-cells into the pancreatic islets. T ype 1 diabetes is an autoimmune disease characterized by T-cell-mediated destruction of the insulin-secreting ␤-cells (1)(2)(3). It is believed that environmental risk factors interact with genetic factors to trigger the development of autoimmunity.…”
mentioning
confidence: 99%
“…However, further studies revealed that results may vary at the level of individual targets, depending on stress intensity or duration (Dohmen 2004;Saitoh and Hinchey 2000;Tempe et al 2008). Human SUMO-1 has been reported to modify Ran GTPase activating protein 1 (RanGAP1) (Matunis et al 1996) and regulate the promyelocytic leukemia (PML)/p53 tumor suppressor network (Fogal et al 2000), whereas SUMO-4 is associated with stress response and type 1 diabetes (Guo et al 2004;Wang and She 2008). Furthermore, SUMO-1 and SUMO-2/3 are ubiquitously expressed, while SUMO-4 seems to be expressed primarily in the lymph node and spleen (Guo et al 2004).…”
Section: Introductionmentioning
confidence: 99%